The Analysis and Evaluation of The Performance of 7 Stage Centrifugal Compressor Apparatus with Variations in Blade Speed and Flow Rate - Alvin; Ahmad Khairul Faizin (Jurnal Rekayasa Mesin, 2025)
Centrifugal compressors have an important role in industry because they function to increase gas pressure through the impeller. However, efficiency and power consumption issues frequently arise, particularly under variations in blade speed and flow rate. Previous studies have mostly employed CFD simulations without direct experimental analysis of blade speed and valve opening on actual compressor performance. This study aims to analyze the performance of a seven-stage centrifugal compressor with variations in blade speed and flow rate through experimental methods to obtain efficient operating conditions. The research method involved collecting data three times with variations in blade speed and valve openings of 50%, 75%, and 100%, and analyzing isentropic efficiency based on motor power. The results showed the highest efficiency of 67% occurred at 550 RPM with a 50% valve opening, while efficiency decreased at 100% valve opening across all RPM levels. Motor power consumption increased from 35 Watts at 450 RPM to 280 Watts at 1350 RPM, but the increase in power was not accompanied by an increase in efficiency, especially at high speeds, which led to turbulence and decreased performance. In conclusion, the optimal compressor performance was achieved at medium blade speeds with partial valve openings, resulting in optimal efficiency and power consumption. These findings can serve as a reference for the design and operation of centrifugal compressors to achieve more energy- and cost-efficient performance.